Analiza rozmycia dna cieku poniżej bystrza o zwiększonej szorstkości (przykład z potoku Poniczanka w miejscowości Ponice) = Gravel bed river scouring analysis downstream of block ramp (example from the Poniczanka stream in Ponice village) - Plesiński, Karol (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The work describes the scouring process downstream of boulder block ramps on Poniczanka Stream in Ponice village. The depth of the down-stream scouring rate was calculated using empirical formulae due to different authors. The results of the calculations were verified basing on the field measurements. Finally only those formulae which results were most consistent with field observations and those with were the worst consistent with field observations are presented along a paper.
Keywords: rozmycie dna; wzory empiryczne; bystrze o zwiększonej szorstkości; Poniczanka (potok); scouring depth; empirical formulas; block ramp; Poniczanka stream